Tenderness, pH and Water Activity (Aw) of Spices Dried Meat on Various Concentrate of Ginger Extract (Zingiber Officinale Roscoe) and Different Soaking Time - Akhadiyah Afrila; Firman Jaya (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2012)
The objectives of current research were to find out the concentrate of Ginger extract (Zingiber officinale Roscoe) and different soaking time of to tenderness, pH, and water activity (Aw), microbial count and sensory evaluation of spices dried meat. The result showed that higher the ginger extract (Zingiber officinale Roscoe) concentrate and longer the soaking time, it would give more tenderness, pH, and water activity (Aw) to spices dried meat with 15% ginger extract (Zingiber officinale Roscoe) extract and 20 minutes length of soaking time. Key Words : Dendeng, ginger, soaking time, tenderness, pH and Aw